RISK FACTORS AND ASSESSMENT OF QUALITY OF LIFE IN STROKE PATIENTS IN VARIOUS OCCUPATIONAL GROUPS - Вишнякова, Татьяна Александровна; Яшникова, Мария Викторовна; Потеряева, Елена Леонидовна (Medicine in Kuzbass, 2023)
The aim of the research – analysis of the distribution of risk factors and quality of life in stroke patients of various occupational groups. Material and methods. 100 stroke patients were examined, who at the time of the development of the disease had been working under the influence of various harmful production factors for more than 5 years and formed the main group. The comparison group consisted of 38 stroke patients who had no contact with harmful production factors. All the examined were men aged from 29 to 59 years. All patients underwent clinical, laboratory and instrumental examinations to identify cardiovascular risk factors. To assess the quality of life («physical component of health» and «psychological component of health») a non-specific questionnaire MOS «Health Status Survey SF-36» was used for a stroke patient during the acute period. The dynamics of changes in the quality of life indicators of the studied groups was traced on the 3rd and 28th days of the disease. Statistical processing of the obtained data was carried out according to generally accepted methods using SPSS Statistical software version 23.0. Results. Arterial hypertension was registered in 100 % of cases in the main group and in the comparison group. In stroke patients who worked in conditions of high occupational risk, smoking and alcohol abuse factors significantly (p < 0.001) prevailed, and a high frequency of dyslipidemia factor was also established. Diabetes mellitus was more often determined in the comparison group. Indicators of quality of life (physical and psychological components of health) in the acute period of stroke in patients of the main group on the 3rd and 28th days of the disease had lower values in comparison with patients of the comparison group. Conclusions. The most significant factors of development in stroke patients of high occupational risk have been identified, which indicates the need for active prevention of the development of hypertension, dyslipidemia, as well as measures to eliminate factors of smoking and alcohol abuse.